(3GdGQJSGeGJ GddWGa aj NGWQ GdMGL Edi CbOS eWGa (B1929 /s - (3CQSdGf, TcjHs (3GdCejQ,s 1869-1946; (3MLGRj, Cjefs 1970- ((3CHh XHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdShjOj ddfTQ hGdJhRjY ,s (3HjQhJ (B- (3dHfGf (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ,s (3YqeGf (B- (3GdCQOf (B:s (3OGQ GdaGQS,s, 2004)
(3jJMOK gPG GdcJGH Yf GdGQJSGeGJ GddWGa aj NGWQ GdMGL Edi CbOS eWGa (B1929 (3MjK cGf GdCejQ TcjH GQSdGf jYjT aj ShjSQG HYjOG Yf GdhWf YfOeG YbO GdYRe Ydi GdbjGe HgPg GdQMdI Ydi GdOjGQ GdebOSI hHOCJ GdQMdI SfI (B1929 (3aj hbJ SHbg GfJRGY Gdedc YHO GdYRjR Hf SYhO ecI ef GdTQja MSjf SfI (B1924 (3hGfWdb GdCejQ aj QMdJg ef dhRGf aj ShjSQG eJLgG Edi fGHhdj GdEjWGdjI hef Ke Edi HhQ SYjO eLJGRG GdShjS Ydi HMQ QGHZ GdCMeQ djUd LOI hefgG Edi ecI hef gfGc SjTQY aj JLhGd Ydi HdOGf hCeGcf YOjOI WGdeG QZH aj GdhUhd EdjgG(B.s
(3GdeMJhjGJ (B: (3GSJgdGd(B-(3GdebOeI(B-(3eSGQ GdQMdI(B-(3OjHGLI GdeDda(B-(3fU GdQMdI(B-(3ef GdSjhjS Edi LOI(B-(3TYhQj Gdbhej aj LOI hGdMLGR(B-(3GdcdGe Ydi ecI GdecQeI(B-(3GdeWhahf aj ecI hGdeRhQhf aj GdeOjfI(B-(3GdcdGe Ydi GdWGFa(B-(3JNWjW GdWGFa hSHH fRhd JKbja HgG(B-(3YQV GdWGFa GdLZQGaj hSHH JCSjSg(B-(3YeQGf LRjQI GdYQH(B-(3GSJWQGO aj bHGFd GdMLGR(B-(3NGJeI GdGQJSGeGJ(B-(3edMbGf(B-(3cTGa MVGQj hagGQS(B.s
(3cTGa (B: (3UaMI (B293-375.s
(3JUeje GdZdGa (B: (3efjQ GdTYQGhj(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdMLs; (3GdCeGcf GdebOSI GdESdGejIs -- (3GdSYhOjIs; (3GdMLGR (B((3GdSYhOjI(B)s -- (3hUa hQMdGJs; (3GdSYhOjIs -- (3JGQjNs